Expansion Dynamic and Characterization of Stagnation Layer in Laterally Colliding Plasmas: Dependence of Observation Bandwidth and Plasma Plume Separation. Issue 1 (1st December 2022) - Al-Juboori, Haider M.; McCormack, Tom
Abstract: The colliding laser-produced plasma (CLPP) has a wide range of applications in various contexts, that might start with astrophysical applications or pulsed laser deposition or Laser-Induced Breakdown Spectroscopy (LIBS), which is a powerful analytical technique for elemental analysis and material identification. In CLPP experiments, the stagnation layer might form at the interface region when two dense laser-induced plasmas collide, and the degree of stagnation can be diagnosed by the collisionality parameter that is used to determine what kind of interaction will take place, i.e., soft or hard stagnation. Our experimental work presents the results of the temporal, spatial and semi-spectrally imaging of colliding plasmas of aluminium and silicon targets. The analysis is focused on describing the velocity of the expanding plasma front for the interaction zone. The aim of the work presented here is to further advance and study colliding plasma techniques, as well as other methods to realize and control species density and expansion, with a view to a deep understanding of these complex mechanisms and optimising emission in the visible wavelength range. All investigation sequences were based on a similar experimental setup, where two different focusing lenses were used with an effective focal length (EFL) of approx. 100mm or 125mm to achieve seed separation around 1.66mm or 2.16mm, respectively. Time-resolved emission imaging was employed to track the stagnation layer‛s size and shape, which might act as a signature of hard versus soft stagnation. The study provides a considerable amount of detailed data related to the expansion velocity of the interaction zone which extends the understanding of the behaviour of particular species within colliding laser-produced plasmas.